Psychotherapy of "emotional coldness" syndrome in a person-centered approach - Терещенко, Н.М. (ХНУ, 2014)
The paper deals with syndrome of "emotional coldness" which hinders the establishment of relations of psychological intimacy in interpersonal relationships. An analysis syndrome "emotional coldness" in the context of person-centered approach. We describe the main factors helping to conduct in person-centered psychotherapy, that overcome such features syndrome "emotional coldness" as distrust of their own feelings, networking relations for a particular scenario, fear of psychological proximity, etc. There are cases of psychological practice
Keywords: syndrome "emotional coldness"; person-centered approach; empathy; congruent; psychotherapy